In Vitro Cultivation of Aphelenchoides besseyi Christie on Fungal Cultures - Annisa Nur Imamah; Supramana Supramana; Tri Asmira Damayanti (Universitas Gadjah Mada, 2020)
White tip disease on rice caused by Aphelenchoides besseyi is categorized as emerging infectious disease in Indonesia because the disease incidence and its geographical distributionare increasing rapidly. Until presently, there is no information related with mass culture technique of Ap. besseyi in Indonesia. Thus, studies to obtain pure population of Ap. besseyi are necessary to be conducted to support various research aspects in the future. This research is aimed to study Ap. besseyi pure mass culture technique by rearing the nematode on three fungal species. Three different fungal cultures on PDA medium, i.e. Alternaria padwickii, Fusarium semitectum, and Botrytis cinerea were tested as Ap. besseyi cultivation media. To obtain the optimum condition for nematode cultivation, the fungal cultures were incubated in three different temperature. The nematodes were surface sterilized with 0.1% streptomycin sulfate followed by washing with sterilized water before infesting the nematode into fungal culture. Subsequently, 25 sterilized nematodes were infested into 7 days old of fungal culture and incubated at 20ºC, 25ºC and 30 ºC. After 21 days, nematodes were harvested and counted the final population. Among fungal species tested as rearing medium, the best culture for Ap. besseyi reproduction was on Al. padwickii culture at 25 ºC with average final population up to 9,115 per petri dish and reproduction factor 364.6. At a 30ºC, Ap. besseyi was failed to develop its population in all the fungal cultures tested. It indicated that the optimum temperature for reproduction of Ap. besseyi on those of fungal species was 20-25 ºC.